Feasibility Study of Various Litho-Fluid Indicators for Better Hydrocarbon Prediction in Malay and Adjacent Basin - Syaza Zuhaira Shamsuddin, Maman Hermana, DP Ghosh, Ahmed Mohamed, . (2017)
The application of lithology and fluid indicators has helped the geophysicists to discriminate reservoirs to non-reservoirs from a field. This analysis is conducted to select the most suitable lithology and fluid indicator for the Malay basin that could lead to better eliminate pitfalls of amplitude.